Guru Kristen Profesional di Era Digital: Sebuah Kajian Filsafat Berdasarkan Wawasan Kristen Alkitabiah - Sembiring, Erina Hannawita; Listiani, Tanti (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2023)
Education always got development and need professional teachers in the application to reach the purpose of education. Through writing this paper will reviewed how a professional teacher is and what the importance to become a professional Christian teacher in digital era reviewed based on biblical Christian worldview. Method that used in writing this paper is literature study method. Based on the result of review in this paper, known that professional teacher is a teacher that mastered all of teacher competence and can follow education development that shown by the teacher competence to use technology. By mastered all of competence that must have by teacher and utilize technology for support the learning process, teacher will be able to create learning process that can reach the purpose of education. The professional teacher will be able to introduce God to their students, and bring students to become person that more like Christ. Be a professional teacher is a responsibility for a Christian teacher in doing their calling, so advice to every teacher to follow trainings that can support teacher become a professional teacher, especially related with information and communication technology.